MACKEREL FISHERY OF CALICUT DURING THE YEARS 1959-60 TO 1967-68 - Venkataraman, G; Rao, K V Narayana (Indian Journal of Fisheries, 2011)
This paper deals with the mackerel fishery of Calicut area for the years 1959-60 to1967-68. Monthly figures of efi'ort, catch and catch/eff'ort for each gear as well as standardeffort, catch and catch/standard efi'ort for each month and each season are given.Though the total landings showed considerable fluctuations from year to year,the catch trends indicated that there was a marked improvement in the fishery everythird year followed by a fall in the catches in the next two successive years. In1959-60, 1961-62, 1962-63 and 1964-65 fishing seasons, when the catch returns werehigh, an increase in effort could have resulted in higher landings